Sales Promotion Influences Impulse Purchases of Products on TikTok Shop - Nyoman Dewi Pitaloka Cahyadi; Ni Putu Dera Yanthi; Putu Ayu Trisna Febrianty (LPPM Universitas 17 Agustus 1945 Semarang, 2026)
Technological developments have led to a shift from traditional sales promotion to digital sales promotion. A new phenomenon has emerged, namely the integration of social media platforms and e-commerce. The purpose of this study is to analyze the effect of sales promotion and positive emotions on impulsive buying, as well as the mediating role of positive emotions on TikTok Shop users in Denpasar. The results of this study were obtained using the SEM-PLS method. The results of this study indicate that positive emotions and sales promotions have a significant influence on impulsive purchasing of products on TikTok Shop, sales promotions have a significant influence on positive emotions when purchasing products on TikTok Shop, and positive emotions can mediate the influence of sales promotions on impulsive purchasing of products on TikTok Shop.